Il dialogo tra le istituzioni: come lo psicologo dell’emergenza facilita la comunicazione tra la popolazione e i sistemi - Benedetta Giacomozzi; Ingrid Tere Powell; Gina Riccio (Rivista di Psicologia dell'Emergenza e dell'Assistenza Umanitaria, 2020)
In a maxi-emergency like an earthquake, the emergency psychologist can facilitate the dialogue within institutions and communities (Giacomozzi et al., 2017). Difficulty of communication between institutions and population can create a fracture: therefore, it becomes important to weave a dialogue that enhances mediation processes as well as the construction of an adaptive system – which can be built through the integration between the natural system (population) and the expert system (rescuers). Following the concept of “Caring Niche” (Axia et al., 2004), we share our experiences during the maxi-emergency of the 2016’s earthquake in Amatrice. On the 24th of August 2016, the activation of our association, Psicologi per I popoli – Trentino ODV, took place differently than usual: our involvement was inside a “technical field”, where different professional groups – such as brigades of the fire, engineers, territorial technicians, psychologists – alternated and cooperated (see Sphere, 2018). After an initial phase of scouting within the camp, our work expanded outside the camp, mainly on three fronts: with school (parents, students, teachers, managers and representatives of Ministero dell’Istruzione, dell’Università e della Ricerca / MIUR), with the population directly affected by the earthquake and finally with Civil Protection technicians and volunteers. The emergency psychologist became a facilitator of communication between the needs of the population and those of the rescue systems (Giacomozzi et al., 2017; Antonello e Viejo, 2013).